Charity hazard : A real hazard to natural disaster insurance? - Paul A. Raschky; Hannelore Weck-Hannemann (University of Innsbruck, Department of Public Finance, 2007)
After the flooding in 2002 European governments provided billions of Euros of financial assistance to their citizens. Although there is no doubt that solidarity and some sort of assistance is reasonable, the question arises why these damages were not sufficiently insured. One explanation why individuals reject to obtain insurance cover against natural hazards is that they anticipate governmental and private aid. This problem became to be known as charity hazard. The present paper gives an economic analysis of the institutional arrangements on the market for natural disaster insurances focusing on imperfections caused by governmental financial relief. It provides a theoretical explanation why charity hazard is a problem on the market for natural disaster insurances, in the way that it acts as an obstacle for the proper diffusion and therefore the establishment of natural hazard insurances. This paper provides a review of the scientific discussion on charity hazard, provides a theoretical analysis and points out the existing empirical problems regarding this issue.
Keywords: Q54; R11; G22; 330; natural hazard insurance; market failure; governmental assistance; Naturkatastrophe; Elementarschadenversicherung; Versicherungsmarkt; Marktversagen; Katastrophenhilfe; Theorie